Qualification requirements for foreign suppliers in public procurement: Evidence from the Czech Republic - Martin Vyklický; Petr Man; Rudolf Franz Heidu; Radek Jurčík (DANUBE: Law, Economics and Social Issues Review, 2016)
Qualification requirements for foreign suppliers in Public Procurement (PP) are quite different in each European Union (EU) member state. The most complex requirements for foreign suppliers in the context of public purchases are included in the Czech PP law. The aim of this paper is to make an overview of the problem of qualification requirements for foreign suppliers in the PP law of the CR. Its sub-objectives are the identification and explanation of solutions to the problem in the PP legislation of neighboring countries of the CR that are also members of the EU. The methodological part of the contribution is based mainly on the analysis and critical evaluation of the current state of legal issues relating to the proof of qualification of foreign suppliers in PP orders of the CR; with examples of fairly extensive decision-making practices of the Office for the Protection of Competition and law courts, including the jurisprudence of the European Court of Justice. The paper highlights the unnecessary complexity of qualification requirements that, on purely formal grounds, inhibits submissions of tenders from potential foreign suppliers that would otherwise be able to submit a bid for a public contract without any problems whatsoever. The authors are using and applying a comparative-legal method in the context of the comparison of the PP legislation of neighboring countries of the CR that are also members of the EU. The case study of foreign suppliers bidding for above-threshold public tenders in the CR at the minimum legal requirements of the contracting authority (CA) for proof of qualification, the comparation study with selected EU countries or analysis of the development of the proportion of public contracts awarded to foreign suppliers in 2010-2014 shows that there is legislation uncertainty in EU PP law that should be reduced and simplified on an EC basis.
Keywords: 330; Qualification Requirements; Public Procurement; Foreign Supplier